2016
DOI: 10.1103/physreva.94.062111
|View full text |Cite
|
Sign up to set email alerts
|

Bounding quantum-gravity-inspired decoherence using atom interferometry

Abstract: Hypothetical models have been proposed in which explicit collapse mechanisms prevent the superposition principle from holding at large scales. In particular, the model introduced by Ellis et al. [J. Ellis et al., Phys. Lett. B 221, 113 (1989)] suggests that quantum gravity might be responsible for the collapse of the wave function of massive objects in spatial superpositions. We consider here a recent experiment reporting on interferometry with atoms delocalized over half a meter for a time scale of 1 s [T. K… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Leggett (2002) claims about the SQUID experiments that "any reasonable" measure for macroscopic quantum states would assign an effective size that is in the order of the number of involved electrons. For the experiments Friedman et al (2000); van der Wal et al (2000), this is 10 10 (in units of Bohr magneton in the case of Leggett's extensive difference). Knee et al (2016) found an extensive difference of roughly 1.3 × 10 5 in units of Bohr magneton for their experiment.…”
Section: Discussion On the Size Of Flux States In Squid Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Leggett (2002) claims about the SQUID experiments that "any reasonable" measure for macroscopic quantum states would assign an effective size that is in the order of the number of involved electrons. For the experiments Friedman et al (2000); van der Wal et al (2000), this is 10 10 (in units of Bohr magneton in the case of Leggett's extensive difference). Knee et al (2016) found an extensive difference of roughly 1.3 × 10 5 in units of Bohr magneton for their experiment.…”
Section: Discussion On the Size Of Flux States In Squid Systemsmentioning
confidence: 99%
“…This number is strongly contrasted by Marquardt et al (2008) using their framework. Analyzing only van der Wal et al (2000), the authors find an effective size between one and two, that is, it suffices to apply at most two basic steps to map, say, the clockwise circulating state to the anticlockwise one. Similarly low is the number found by Nimmrichter et al (2011), who assign an effective size of µ ≈ 5 to the experiment of Friedman et al (2000).…”
Section: Discussion On the Size Of Flux States In Squid Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Decoherence, here, is modelled by a single phenomenological parameter [56] which represents the interaction between the one-particle system and its environment. The environment can be attributed to quantum gravity effects [57][58][59][60][61][62][63][64] or it can be due to detector background itself. Apart from decoherence, we also include the effects of CP violation.…”
Section: Introductionmentioning
confidence: 99%
“…by atom interferometers with large momentum transfers, yielding large spatial separations [5,46]. In particular, we are currently evaluating [47] what are the contraints on the model of Ref. [11] imposed by the experimental results published very recently in Ref.…”
mentioning
confidence: 99%